Mass Media and «the Сolor Revolutions» - - Zhao Yonghua (Vestnik RUDN. International Relations, 2010)
This article discusses the importance and influence of media on the progress of «color revolutions» based on patterns of media and political reforms in the state, industrial development of mass media and media strategy of the Western States (as an example the U.S.) in relation to Commonwealth countries.